MON-490 Iatrogenic Hypophosphatemia Presenting as Low Bone Mass - Sharma, Shiksha (J Endocr Soc, 2019)
Introduction: The incidence of osteomalacia is 1 in every 1000 individuals and the most common cause is vitamin D deficiency. Hypophosphatemia is a less recognized but important etiology of osteomalacia. Here we describe a case who was referred to Endocrinology for osteoporosis but was found to have medication induced hypophosphatemic osteomalacia. Case: A 68 years old woman from Thailand with known past medical history of chronic hepatitis B infection, Sjogren’s syndrome, lung cancer s/p lobectomy had screening DEXA scan which showed T score of -2.9SD at Forearm. She was referred to Endocrinology for osteoporosis work up. She reported at least 8-month long history of myalgia and noticed pain in the chest wall exacerbated by motion such as rolling in bed for the last few months. Blood work showed normal calcium, robust vitamin D and high bone specific alkaline phosphatase levels. Phosphorus levels were noted to be in the range of 1.4 to 2.1 mg/dl for 2 years before the presentation and fractional excretion of phosphorous was 71%. Bone scan showed foci of increased radiotracer uptake in multiple ribs which correlated to the site of prior thoracotomy. Patient was taking adefovir 10 mg daily for 4 years for hepatitis B infection which is known to cause increased renal phosphate loss similar to Fanconi’s syndrome. The medication was changed and phosphate repletion was started which alleviated the symptoms promptly. Discussion: This case emphasizes on the importance of considering osteomalacia as a potential cause of low bone mass. Adefovir is commonly used for hepatitis B treatment and is known to cause renal phosphate loss at higher doses like 20-40 mg a day. This case illustrates that it can cause similar phosphoturic effect even at lower doses if used over a long period of time as a result of the cumulative dose effect of this drug. It is important to be cognizant of this side effect of Adefovir as it is a widely used medication and monitor patients for hypophosphatemia while undergoing therapy.